Genetic diversity analysis of Exobasidium vexans causing tea blister blight in Wonosobo, Central Java, Indonesia using RAPD markers. (27th June 2022) - Rachmad, Fahreza Deliar; Priyatmojo, Achmadi; Widiastuti, Ani
Abstract: Exobasidium vexans, causing tea blister blight, is an obligate parasitic fungus and one of the most detrimental pathogens in most tea plantations in Asia. Information about genetic diversity of E. vexans is necessarily needed to develop disease management based on pathogen evolution. This study aimed to understand the genetic diversity of E. vexans from three different locations in Wonosobo, Central Java, and Indonesia. Isolates used in this study were collected from blister light symptomized leaves, in three different locations. Isolates were identified using morphological indicators and DNA sequencing, and then genetic diversity was analysed using RAPD markers. Basidiospore size and shape were not different among isolates. Molecular identification based on ITS genes confirmed that ten isolates causing tea blister blight taken from the three locations were E. vexans. Clustering analysis indicates recombination occurred which triggered the high genetic diversity among samples. The polyculture system may have caused high genetic diversity.